1998
DOI: 10.1111/j.1600-0773.1998.tb01471.x
|View full text |Cite
|
Sign up to set email alerts
|

NADH: Ubiquinone Oxidoreductase Inhibitors Block Induction of Ornithine Decarboxylase Activity in MCF‐7 Human Breast Cancer Cells*

Abstract: Abstract:Rotenone is the classical inhibitor of NADH : ubiquinone oxidoreductase and its analogue deguelin is a potent inhibitor of 12-0-tetradecanoylphorbol 13-acetate (TPA)-induced ornithine decarboxylase mRNA steady state level and enzyme activity in mouse 308 cells (Gerhauser et al. 1995). In MCF-7 human breast cancer cells, rotenone, deguelin and two structurally-unrelated miticides (pyridaben and fenazaquin) inhibit not only NADH: ubiquinone oxidoreductase but also induced ornithine decarboxylase activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…1A, rotenone dose-dependently increased histone-associated DNA fragmentation. However, dopaminergic SH-SY5Y cells are far more vulnerable to rotenone than breast cancer MCF-7 cells and hepatoma HepG2 cells despite the fact that rotenone inhibits mitochondrial complex I in these cells and produces ROS (Rowlands and Casida, 1998;Greenamyre et al, 2003). We also ascertained that apoptosis of SH-SY5Y cells was induced by rotenone using another technique.…”
Section: Resultsmentioning
confidence: 89%
“…1A, rotenone dose-dependently increased histone-associated DNA fragmentation. However, dopaminergic SH-SY5Y cells are far more vulnerable to rotenone than breast cancer MCF-7 cells and hepatoma HepG2 cells despite the fact that rotenone inhibits mitochondrial complex I in these cells and produces ROS (Rowlands and Casida, 1998;Greenamyre et al, 2003). We also ascertained that apoptosis of SH-SY5Y cells was induced by rotenone using another technique.…”
Section: Resultsmentioning
confidence: 89%
“…Similarly, oxygen consumption by intact cells was inhibited by short-term exposures to ATRA, 114 phenyethyl isothiocyanate, 207 CD437, 114 4HPR, 115 deguelin, 117 rotenone, 118 capsaicin, 116 and resiniferatoxin. 116 The interruption of biochemical processes associated with OXPHOS (e.g., substrate oxidation, oxygen consumption, the maintenance of m , ATP synthesis, or ATP/ADT exchange) has been reported in isolated mitochondria and/or submitochondrial particles exposed to ATRA, 131 curcumin, 155 benzyl isothiocyanate, 208 tamoxifen, 125,209 genistein, 126 resveratrol, 126 capsaicin, 129,204,205 deguelin, 126,210,211 and rotenone. 126,129,210,211 Mitochondrial swelling has been observed in isolated mitochondria exposed to CD437 212 curcumin, 155,213 and benzyl isothiocyanate.…”
Section: Class Agent Proposed Mechanismsmentioning
confidence: 98%
“…Complex I inhibitors rotenone, piericidin A, and amytal have been used in co-treatment with DES and/or estrogens to elucidate the site of estrogen action on electron transfer [28,39]. In MCF7 cells, it was demonstrated that co-treatment with rotenone (10 nM) and E2 (10 nM) strongly inhibited ornithine decarboxylase activity by 86% [42]. More recently, a study reported that treatment with 10 μM of 2-methoxyestradiol (2-Me) induced apoptosis in Ewing sarcoma cells through hydrogen peroxide (H 2 O 2 ) production [43].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence in support of a ROS signal transduction pathway originating from complex I comes from a study which reported that the mitochondrial complex I inhibitor, rotenone, blocked ROS mediated signaling. Interestingly, this study demonstrated that a co-treatment of rotenone (10 nM) and E2 (10 nM) inhibited ornithine decarboxylase activity by 86% in MCF7 cells [42]. Since ornithine decarboxylase activity is a marker for cell growth, it appears that a signal transduction pathway for estrogen-induced cell growth may originate from the mitochondria assuming that rotenone inhibition is specific to complex I.…”
Section: Introductionmentioning
confidence: 99%